p, Pengaruh Realisasi Gaji Guru Terhadap Mutu Pendidikan Islam: Tinjauan Literatur Manajemen Pembiayaan Pendidikan: Realisasi Gaji Guru - Hasibuan, Nasrin; Hamdi Abdul Karim; Jefri Hasibuan; Ali Mustopa Yakub Simbolon (Global Action and Education for Society, 2026)
Teacher welfare is a major concern in improving the quality of Islamic education. Low welfare, both financially and non-financially, negatively impacts teacher motivation and performance in the learning process. This study aims to analyze the impact of teacher salary realization on the quality of Islamic education. This research uses a qualitative approach through literature review, reviewing more than 20 academic sources, including scientific journals, books, and related policy documents. The results indicate that teacher salaries, as a form of compensation, play a crucial role in shaping teacher welfare and professionalism. In the Islamic context, the salary system is governed by the ijarah principle, which emphasizes fairness and equity. This study concludes that effective, equitable, and sustainable financial management is essential to ensure teacher welfare and improve the overall quality of Islamic education.